2022
DOI: 10.1101/2022.04.16.488543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone marrow haematopoietic stem cells influence liver homeostatic networks and cancer development

Abstract: In fatty liver disease, systemic homeostasis is perturbed. While pre-clinical models are used to understand its pathogenesis, translating this knowledge to patients is difficult. However, by focusing on the most preserved homeostasis systems between species and models, novel disease dimensions can be unearthed. We interrogated core liver gene co-expression networks in a mouse model of liver cancer following dietary challenge. The behaviour of immunometabolic networks in tumours mirrored their counterparts in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 56 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…We showed that mere dysregulation in cholesterol homeostasis was not sufficient to incite BM HSPC responses in mice, while suppression of bile acid biosynthesis was . Of note, we have previously shown the protective effects of inhibiting bile acid and cholesterol biosynthesis on reducing liver cancer burden 1 . Interestingly, a recent analysis of patients in the IMBrave 150 clinical trial (immunotherapy in HCC) showed that responders had down-regulation in pathways related to cholesterol homeostasis and bile acid synthesis 13 .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We showed that mere dysregulation in cholesterol homeostasis was not sufficient to incite BM HSPC responses in mice, while suppression of bile acid biosynthesis was . Of note, we have previously shown the protective effects of inhibiting bile acid and cholesterol biosynthesis on reducing liver cancer burden 1 . Interestingly, a recent analysis of patients in the IMBrave 150 clinical trial (immunotherapy in HCC) showed that responders had down-regulation in pathways related to cholesterol homeostasis and bile acid synthesis 13 .…”
Section: Discussionmentioning
confidence: 96%
“…Fatty liver disease associated with metabolic dysregulation also shares these common risk factors. In a previous study we reported the bone marrow haematopoietic responses in mice that develop fatty liver-related liver cancer while on diets of varying composition 1 . However, that study did not allow us to distinguish whether dietary composition exerts effects on the liver and marrow independent of tumour presence, nor could we deduce if liver tumours per se could regulate this process.…”
Section: Dietary Composition Rather Than Presence Of Tumour Regulates...mentioning
confidence: 99%
See 3 more Smart Citations